La imputación objetiva y el principio de confianza en los delitos contra la eficiencia de la Administración Pública. - Chuncho Jiménez, Iván David (2023)
This Curricular Integration Work was carried out in order to contribute to the fight against corruption due to the increasingly recurring cases involving the Public Administration. In this regard, the proper assessment of dogmatic categories such as unbiased accusations plays a fundamental role in defining responsibilities when criminal acts occur; therefore, it is crucial to be acquainted and understand the aspects that play a role on this matter in order to adequately understand its use and scope in civil servant crimes. Within this framework, this investigation includes several research material as well as different bibliographic references, both digital and physical; in addition, a current national and comparative legislation is presented, which also contributes to the analysis. Likewise, the analytical, scientific, comparative, synthetic, statistical, inductive and deductive methods were used. Finally, in agreement with the doctrinal investigative work, the documentary was used as the ideal technique to understand the scope of theoretical assessment as well as their limitations in specific cases, strongly supported criteria plus as well as interviews with some legal professionals which highlighted the importance of evaluating the institutes that encompass unbiased accusation, how it is used and its relationship in crimes against the efficiency of the Public Administration. The aforementioned background allowed carrying out a synthetic analysis based on the law, doctrine, casuistry and experience, which substantially enhanced the discussion; moreover, a series of evaluative conceptions regarding the use of unbiased accusations with a focus on the principle of trust. Additionally, specific recommendations gathered throughout the investigation process. Finally, provide a series of practical proposals, hopefully essential for the future which might lead to further investigations regarding the aim of unbiased accusation and crimes against the efficiency of the Public Administration.